The effectiveness of problem-based learning models using a steam approach to improve students' mathematical modeling ability on static electricity materials - Hardiana, Helsi; Sitompul, Stepanus Sahala; Hamdani, Hamdani (IAIN Palangka Raya, 2024)
This study aims to determine the effectiveness of the PBL model with the STEAM approach to improving students' mathematical modeling ability (MMA) on static electricity material at SMP Negeri 2 Pontianak. This form of research is a pre-experimental design type one-group pretest-posttest design. The research sample was class IXB students at SMP Negeri 2 Pontianak (32 people), with a cluster random sampling technique. The instruments used are tests and questionnaires. Based on the results of the Wilcoxon Test, Asymp values. Sig (2-tailed) of 0.000 (z< 0.05) shows that there are differences in the mathematical modeling ability of students in the pretest and posttest, with the level of effectiveness being in the very high category (d = 5.49). Based on response questionnaire data, 97% of students responded well to treatment, and 3% were in a suitable category. The study's conclusion is applying the PBL model with a practical STEAM approach to improving the mathematical modeling ability of students on static electricity material at SMP Negeri 2 Pontianak.